1991
DOI: 10.1002/mds.870060105
|View full text |Cite
|
Sign up to set email alerts
|

The hemodynamic effects of triglycyl‐lysine‐vasopressin (glypressin) in patients with parkinsonism and orthostatic hypotension

Abstract: The hemodynamic effects of triglycyl-lysine-vasopressin (TGLVP) were investigated in a single-blind study in seven patients with chronic orthostatic hypotension and parkinsonism. Blood pressure, heart rate, and stroke volume were measured in the supine position before and after bolus injection of either placebo or TGLVP (5.0, 7.5, or 10.0 micrograms/kg of body weight). After 40 min in the supine position, the patients were head-up tilted to 45 degrees for 20 min. All patients underwent four tilt studies with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although not widely used, the vasopressor effect of terlipressin has been previously reported. Rittig et al 19 demonstrated the beneficial vasopressor effects of terlipressin in patients with orthostatic hypotension due to Parkinson's disease 19 . Eyraud et al successfully managed intraoperative hypotension with 1 mg terlipressin boluses in 51 vascular surgery patients who were chronically treated with ACE inhibitors or ATIIreceptor antagonists 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Although not widely used, the vasopressor effect of terlipressin has been previously reported. Rittig et al 19 demonstrated the beneficial vasopressor effects of terlipressin in patients with orthostatic hypotension due to Parkinson's disease 19 . Eyraud et al successfully managed intraoperative hypotension with 1 mg terlipressin boluses in 51 vascular surgery patients who were chronically treated with ACE inhibitors or ATIIreceptor antagonists 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Terlipressin, on the other hand, is a potent vasopressin V1-receptor agonist used in patients with hepatorenal syndrome. It has a potent pressor effect in patients with neurogenic OH when given intravenously 24 but is not available in oral form. Additionally, and very importantly, we do not know the long-term impact of therapy on patientreported outcomes, functional outcomes (injurious falls, syncope, cognition), or cardiovascular outcomes.…”
Section: ■ Management Of Orthostatic Hypotensionmentioning
confidence: 99%